2013
DOI: 10.1007/s00405-013-2465-5
|View full text |Cite
|
Sign up to set email alerts
|

Expression of stefin A is of prognostic significance in squamous cell carcinoma of the head and neck

Abstract: Lysosomal proteases cathepsins B and L (CB, CL) and their endogenous inhibitors stefins A and B (SA, SB) are associated with tumor cell invasion and metastasis. The purpose of this study was to determine the immunohistochemical (IHC) localization of these parameters in tissue sections of 65 patients with operable head and neck squamous cell carcinoma (HNSCC) and to evaluate the prognostic significance of the observed IHC reactions. In SCC cells, a dot-like staining pattern for CB and CL was especially polarize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…(19)(20)(21)(22) Cathepsin B expression in patients with PDAC is related to prognosis and recurrence, (23)(24)(25) although the mechanism remains to be elucidated. Cystatin A expression has been observed in tumor tissues, such as breast, (26) head and neck, (27) and lung (28) cancers, as well as hepatocellular carcinoma. (29) In the current study, cathepsin B was expressed in tumor cells, as well as tumor-infiltrating immune cells, especially macrophages, in PDAC tissues.…”
Section: Discussionmentioning
confidence: 99%
“…(19)(20)(21)(22) Cathepsin B expression in patients with PDAC is related to prognosis and recurrence, (23)(24)(25) although the mechanism remains to be elucidated. Cystatin A expression has been observed in tumor tissues, such as breast, (26) head and neck, (27) and lung (28) cancers, as well as hepatocellular carcinoma. (29) In the current study, cathepsin B was expressed in tumor cells, as well as tumor-infiltrating immune cells, especially macrophages, in PDAC tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of immunohistochemistry for head and neck cancers the levels of cathepsins and stefins A and B were examined (Anicin et al, 2013). Stefin A immunopositivity correlates with a favorable outcome in this study of head and neck cancer.…”
Section: Type I Cystatinsmentioning
confidence: 99%
“…In breast cancer, elevated levels of stefin A were suggested to have an inverse correlation with metastatic potential and clinical prognosis (Parker et al, ). However, in head and neck squamous cell carcinoma (Aničin et al, ), increasing stefin A levels have been demonstrated to be positively correlated with tumor prognosis. The clinical significance of the down‐ and up‐regulated stefin B expression levels have also been indicated in colorectal carcinoma (Koshiyama et al, ), gastric cancer (Song et al, ), esophageal carcinoma (Zhang et al, ) and prostatic adenocarcinoma (Mirtti et al, ).…”
mentioning
confidence: 99%